Estimate Model of Sales Forecast By Using Goal programming Method ( Case Study In Forat Factory to Pure Water) - الخفاجي, واثق حياوي لايذ (University of Thi-Qar Journal of Science, 2013)
The sales forecast lead to improve planning process in any industrial or service organization, especially after use quantity methods in forecast process, the organization can estimate profit and production costs from through forecast process. The research includes using goal programming method to find regression parameters and compared the results,which obtained with regression classic methods , and use predication values in sales forecast model for Forat factory , which product pure water with two types bottlefuls once size ( 0.5 )litter and other size ( 1.5 ) litter after addition constrains and goals factory management . The model solve by goal programming method with aid of computer simulation program (Win QSB), theresults explain effect sales final values with constrains and goals factory management.